Raising the bar: Trends in implementing productivity initiatives in the finance and accounting function - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2014)
Faced with a tightening labour supply, raising productivity has become an increasingly important issue for manybusinesses in Singapore. To understand how this impacts the finance and accounting functions of businesses,the Institute of Singapore Chartered Accountants (ISCA) collaborated with Robert Half to survey over 550senior finance executives in Singapore and also the region to understand the focus of finance and accountingfunctions of businesses regarding raising productivity of these departments or functional units.